Analysts' industry expertise - Kadan, Ohad; Madureira, Leonardo; Wang, Rong; Zach, Tzachi (Journal of Accounting and Economics, 2012)
Industry expertise is an important aspect of sell-side research. We explore this aspect using a novel dataset of industry recommendations, which are often issued by strategy analysts. We study sell-side analysts' ability to rank industries relative to each other (across-industry expertise), and how it relates to analysts' ability to rank firms in a particular industry (within-industry expertise). We find that analysts express more optimism towards industries with higher levels of investment, past profitability, and past returns. Analysts exhibit across-industry expertise, as portfolios based on industry recommendations generate abnormal returns over both short and long horizons, beyond what would be explained by industry momentum. Additionally, industry recommendations contain information, which is orthogonal to the information revealed in firm recommendations, and more so for brokers who benchmark their firm recommendations to industry peers. Consequently, the investment value of sell-side analysts' recommendations is enhanced when both dimensions of industry expertise are utilized by considering industry and firm recommendations in combination.